Asynchronicity and coordination in common and opposing interest games - Riccardo Calcagno; Takuo Sugaya; Yuichiro Kamada; Stefano Lovo (Theoretical Economics, 2014)
We study games endowed with a pre-play phase in which players prepare the actions that will be implemented at a predetermined deadline. In the preparation phase, each player stochastically receives opportunities to revise her actions, and the finally-revised action is taken at the deadline. In 2-player “ common interest" games, where there exists a best action profile for all players, this best action profile is the only equilibrium outcome of the dynamic game. In “ opposing interest" games, which are 2× 2 games with Pareto-unranked strict Nash equilibria, the equilibrium outcome of the dynamic game is generically unique and corresponds to one of the stage-game strict Nash equilibria. Which equilibrium prevails depends on the payoff structure and on the relative frequency of the arrivals of revision opportunities for each of the players.
Keywords: C72; C73; 330; Revision games; pre-opening; finite horizon; equilibrium selection; asynchronous moves